PENGARUH IT CAPABILITY, TRUST, DAN WORK ABILITY TERHADAP KINERJA KARYAWAN PT. BANK TABUNGAN NEGARA (PERSERO) TBK CABANG PEMUDA SURABAYA - Ogya Aryasatya; Siti Mujanah (Cahaya Ilmu Bangsa, 2024)
This research aims to prove and analyze the influence of IT capability, trust and work ability on employee performance. This research was conducted at PT. Bank Tabungan Negara (Persero) Tbk Pemuda Surabaya Branch with a sample size of 57 respondents collected using a questionnaire and the analysis techniques used were validity test, reliability test, classical assumption test, multiple linear regression test, and hypothesis test using SPSS 25. Type This research is quantitative. The research results show that the IT capability variable partially has a positive and significant effect on employee performance, the Trust variable partially has a positive effect on employee performance, the Work Ability variable partially has a positive and significant effect on employee performance. The f test shows that IT Capability, Trust and Work Ability have a positive and significant effect on employee performance at PT Bank Tabungan Negara (Persero) Tbk Pemuda Surabaya Branch.